Does a physiotherapy programme of gross motor training influence motor function and activities of daily living in children presenting with developmental coordination disorder? - Sonill S. Maharaj; Riona Lallie (AOSIS, 2016)
Background: Children with developmental coordination disorder (DCD) lack motor coordination and have difficulty performing motor skills and activities of daily living. Research shows these children do not outgrow their motor difficulties and without intervention do not improve. Physiotherapy is relevant for these children, but due to limited clinical protocols for DCD the aim of this study was to determine the effect of a gross motor training programme for 6-12-year-old children with DCD. Methods: This randomised pre-test, post-test study recruited 64 children with scores of 15th percentile or below using the Movement Assessment Battery for Children (M-ABC). The children were divided equally into an intervention group receiving 8 weeks of gross motor training for core stability, strengthening exercises, balance and coordination with task-specific activities for 30 min per week, while the control group continued with general therapy and activities of daily living. The M-ABC and Developmental Coordination Disorder Questionnaire (DCDQ) were used to assess each child before and after 8 weeks. Results: Sixty children completed the study, with 43 males and 17 females (mean age 10.02 years, SD = 2.10). There were no adverse reactions to the programme and M-ABC scores for the intervention programme improved by 6.46%, ball skills (3.54%) and balance (4.80%) compared with the control (0.17%) and (0.15%), respectively. There were significant (p < 0.05) improvements in DCDQ scores, but teachers allocated lower scores than parents. Conclusion: This study supports 8 weeks of gross motor training which can be a beneficial intervention for physiotherapists to improve gross motor function for DCD. Keywords: Developmental, co-ordination, skills, motor